Seasonal dynamics of bacterial communities in mangrove sediments of Shupaisha island, Zhejiang Province, China - He, Maoqiu; Jiang, Shoudian; Li, Xiangfu; Yao, Liqin; Shui, Bonian (Frontiers in Microbiology, 2025)
Mangrove forests, found primarily in tropical and subtropical coastal regions, support diverse microbial communities that are crucial for nutrient cycling and energy flow and then sustain mangrove ecosystem integrity. This study investigated the seasonal dynamics of bacterial communities in mangrove sediments of Shupaisha island (Zhejiang Province, China) through amplifying and high-throughput sequencing bacterial 16S rRNA gene fragments. Proteobacteria (23.59–44.40%), Actinobacteria (4.92–19.01%), and Bacteroidetes (4.31–22.79%) dominated the bacterial phyla in Shupaisha mangrove sediments with the highest diversity indices in winter. Actinobacteria were more abundant during winter (13.27%) and spring (14.36%), while Bacteroidetes abundance was highest in summer, significantly correlating with temperature. Significant differences in bacterial community composition were observed between winter and summer, while spring and autumn exhibited similar distribution, indicating a transitional pattern in bacterial community dynamics, with temperature and sand content being the most influential factors. This study enhances our understanding of the seasonal characteristics of bacterial communities in the mangrove ecosystems, potentially providing valuable insights into monitoring and assessing the health and stability of mangrove ecosystems in Zhejiang Province.